Elogio de la tolerancia (y de la imperfección) - Pereira Menaut, Antonio-Carlos (Mercurio Peruano, 2013)
Our societies seem to be characterised by wild “hyperpluralism” and toleration. Yet, on closer inspection we may see that we are undergoing tough times for toleration, as the self contradictory idea of “zero toleration” suggests. This is due to widespread attitudes of legalism, hysteric anti-terror policies, safety at all costs, “historic memories”, and new-brand perfectionism and puritanism. Toleration grows only where people have deeply rooted attitudes of common sense, dignity, respect for all persons, reasoning by analogy (rather than by evidence), a wise knowledge of human nature, and a correlative acceptance of its native imperfection.
Keywords: toleration, zero toleration, respect, dignity, common sense